THE PERSON GUILTY IMPROVEMENT WITHOUT ADDRESSING THE ISSUE OF CRIMINAL PROCEDURE FINISH - Tangriev Jasur Olimovich (International Journal of Business, Law and Political Science, 2024)
Objective: This article examines the historical development of the Institute for the termination of criminal proceedings without resolving guilt in criminal procedure legislation, aiming to identify issues and propose effective solutions. Method: The analysis involved reviewing scientific opinions on the institute, studying the gaps in national legislation, and critically assessing the legal and procedural frameworks surrounding case terminations. Results: The study identified significant loopholes and inaccuracies in the legislation, highlighting procedural deficiencies and the need for amendments. Suggestions for legislative improvement were also proposed. Novelty: The article provides a unique perspective on enhancing the effectiveness of the institute by addressing specific shortcomings in the legal framework, contributing valuable insights for the development of criminal procedure legislation.